Search for the Standard Model Higgs boson in the H -> tau(+)tau(-) decay mode in root s=7 TeV pp collisions with ATLAS - Aad, G; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Acerbia, E; et al. (2012)
A search for the Standard Model Higgs boson decaying into a pair of τ leptons is reported. The analysis is based on a data sample of proton-proton collisions collected by the ATLAS experiment at the LHC and corresponding to an integrated luminosity of 4.7fb-1. No significant excess over the expected background is observed in the Higgs boson mass range of 100-150 GeV. The observed (expected) upper limits on the cross section times the branching ratio for H → τ+τ- are found to be between 2.9 (3.4) and 11.7 (8.2) times the Standard Model prediction for this mass range.